Using Corel Draw In Modern Mapping(Application In Geographical Health Mapping) - Al-Tuama, Husam; Rasheed, Shatha (Iraqi Journal of Science, 2024)
The development of the mapping from traditional methods (manual) to themodern drawing methods (Computer) is an important step in the mapping, as themodern digital maps play a big role in the geographical analyses in all branches.There are many software in this field have been used such as Corel Draw which isused for geographical health mapping, through which has been mapping thePrevalence of cancer infections in Iraq based on the Central Statistical Organizationdata taken from the Ministry of Health data which showed the number of cancerdiseases in all area of Iraq for 2005 and 2006, through drawing two maps and use themethods of circles and survey shading in the cartographic representation. Afteranalyzing the two maps we observed that the highest number of infections in cancerdiseases was in Baghdad and these numbers are increasing in (Karkuk, Baghdad,Basrah, Babil, Najaf) and these numbers are decreasing in (Arbil, Sulaymaniyah,Anbar).